Efficacy of Kremah (Alternanthera sp.) Leaf Extract in Reducing Methomyl-Induced Effects on Leukocyte Response in Nile Tilapia (Oreochromis niloticus) - Fathiyah, Dinda Nurul; Ramadhani, Ayu Winna; Islamy, R Adharyan; Aisyah, Diana; Hasan, Veryl (Study Program of Aquaculture, Department of Fisheries and Marine Science, Faculty of Agriculture, University of Mataram, 2026)
Intensification of tilapia (Oreochromis niloticus) farming around agricultural land increases the risk of contamination by the toxic and genotoxic pesticide methomyl, which can trigger oxidative stress, and immune system disorders. The use of natural materials with antioxidant potential, such as kremah (Alternanthera sp.) leaf extract, is an alternative to mitigate these effects. This study was conducted to evaluate the effect of immersion in kremah leaf extract on the leukocyte differential of tilapia exposed to methomyl. A completely randomized design was applied, consisting of four treatments with three replications, namely control, and doses of 20, 30, and 40 ppm. The fish were exposed to 3.2 ppm methomyl for 96 hours and then immersed in the extract for 14 days. The observed parameters comprised leukocyte differential, clinical signs, and water quality, all of which were analyzed using one-way ANOVA followed by an LSD test (p < 0.05). The findings indicated that methomyl exposure led to an increase in monocytes while reducing lymphocyte levels. Immersed in 40 ppm extract for 14 days provided the best results by decreasing monocytes (4.00%), as well as increasing lymphocytes (82.00%) and hemoglobin levels to near normal. It was concluded that kremah leaf extract effectively mitigates oxidative stress and genetic damage caused by methomyl, with an optimal dose of 40 ppm for 14 days.